Dynamic Modeling of a Parabolic Trough Solar Thermal Power Plant with Thermal Storage Using Modelica - Montañés, Rubén M.; Windahl, Johan; Pålsson, Jens; Thern, Marcus (Heat transfer engineering, 2018)
Concentrating solar power (CSP) technology with thermal energy storage is a renewable and emerging technology. In this work, dynamic models for analyzing and evaluating energy storage concepts and its interaction with the solar field and the power block have been developed. A physical model of a 50 MW CSP plant has been implemented in the modeling language Modelica. The models are developed in a modular, flexible structure with a well-defined interface to easily replace and test modules of various detail and complexity. Models include turbine island, steam generator, solar field, and thermal energy storage system. In addition, a decentralized control configuration has been developed. Results have been successfully validated against the reference plant key steady-state data. Dynamic response of the power block has shown expected behavior, and transient durations were comparable with settling times predicted in literature. Furthermore, the performance of the plant has been evaluated during a typical summer day including effects such as variation of solar irradiance, charging and discharging the heat storage system, and dumping excess heat in the solar field. The summer day scenario results agreed with published performance of the plant.